Directed Plateau Search for MAX-k-SAT - Sutton, Andrew; Howe, Adele; Whitley, L. (Proceedings of the International Symposium on Combinatorial Search, 2010)
Local search algorithms for MAX-k-SAT must often explore large regions of mutually connected equal moves, or plateaus, typically by taking random walks through the region. In this paper, we develop a surrogate plateau "gradient" function using a Walsh transform of the objective function. This function gives the mean value of the objective function over localized volumes of the search space. This information can be used to direct search through plateaus more quickly. The focus of this paper is on demonstrating that formal analysis of search space structure can direct existing algorithms in a more principled manner than random walks. We show that embedding the gradient computation into a hill-climbing local search for MAX-k-SAT improves its convergence profile.